INFLUENCE OF PRICE, ADVERTISING AND PRODUCT QUALITY ON CHOCOLATE PURCHASE DECISIONS SILVERQUEEN AT PT KOTA MAS PERMAI - Faris, Salman; Leeman, Wilbert; Aurea, Clarence; Chandra, Florencia (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2023)
In Medan City, PT Kota Mas Permai sells Silverqueen Chocolate. This study's goal was to determine how Silverqueen Chocolate's price, advertising, and product quality affected consumers' choices to buy the chocolate at PT Kota Mas Permai. The association between two or more study variables is demonstrated using the method of quantitative research. Quantitative data are the data type, and primary and secondary data are the data sources. The population is 95 customers of PT Kota Mas Permai and the sampling technique is saturated and the population is used as a sample and 30 people are tested for validity and reliability at PT. Inti Cakrawala Citra. The model with multiple linear regression. The result is that price, advertising and product quality have a partial and simultaneous effect on the purchasing decision of Silverqueen Chocolate at PT Kota Mas Permai.